Theoretical Elucidation of β-O-4 Bond Cleavage of Lignin Model Compound Promoted by Sulfonic Acid-Functionalized Ionic Liquid - Zhang, Yaqin; Huo, Feng; Wang, Yanlei; Xia, Yu; Tan, Xin; Zhang, Suojiang; He, Hongyan (Frontiers in Chemistry, 2019)
While the depolymerization of lignin to chemicals catalyzed by ionic liquids has attracted significant attention, the relevant molecular mechanism, especially the cleavage of specific bonds related to efficient depolymerization still need to be deeply understood for the complexity of this natural aromatic polymer. This work presents a detailed understanding of the cleavage of the most abundant β-O-4 bond in the model system, guaiacylglycerol β-guaiacyl ether, by a Brønsted acidic IL (1-methyl-3-(propyl-3-sulfonate) imidazolium bisulfate ([C3SO3Hmim][HSO4]) using density functional theory calculation and molecular dynamics simulation. It is found that [C3SO3Hmim][HSO4] generates zwitterion/H2SO4 via proton transfer with an energy barrier of 0.38 kcal/mol, which plays a dominant role in the lignin depolymerization process. Subsequently, the reaction can be carried out via three potential pathways, including 1) the dehydration of α-C-OH, 2) dehydration of γ-C-OH, and 3) the protonation of β-O. The electrophilic attack of H2SO4 and the hydrogen-bonding interaction between GG and zwitterion are the two most important factors to promote the depolymerization reaction. In all steps, the dehydration of α-C-OH route is computed to be favored for experiment. The relatively higher energy barrier for β-O-4 bond dissociation among these reaction steps is attributed to the hindrance of the self-assembled clusters of GG in the mixed system. Further, the dense distribution of H13([C3SO3Hmim]) surrounding O21(GG) indicated by sharp peaks in RDFs - reveals that -SO3H in cations plays a substantial role in solvating lignin. Hopefully, this work will show new insights into lignin depolymerization by functionalized ILs in biomass conversion chemistry.